Adjudicating environmental tort cases in China: burden of proof, causation, and insights from 513 court decisions. Issue 2 (November 2018) - Yang, Fan; Zhang, Ting; Zhang, Hao
Abstract : Developing countries and countries with economies in transition have varying experiences in enforcing their national environmental law. China's judicial interpretations and legislation on environmental protection have established the rules that shift the burden of proof for causation in environmental tort litigation. However, this study of 513 court decisions from the people's courts at different levels in China shows that although the court decisions usually refer to or quote the rules that shift the burden of proof, in most cases the victim-plaintiffs still bear the liability to prove whether the causal relationship exists between the pollution and the harm. This study also finds that Chinese courts defer greatly to the evaluation report in proving causation. It suggests that the court practice of adjudicating environmental tort cases in China values more the factual causation of a pollution incident than the provisions regarding proof of causation stipulated by relevant laws. Consequently, such judicial practices hinder the effectiveness of judicial remedies for pollution victims in China.